2009
DOI: 10.1677/erc-08-0219
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that androgen-independent stromal growth factor signals promote androgen-insensitive prostate cancer cell growth in vivo

Abstract: Activation of tumor-stromal interactions is considered to play a critical role in the promotion of tumorigenesis. To discover new therapeutic targets for hormone-refractory prostate tumor growth under androgen ablation therapy, androgen-sensitive LNCaP cells and the derived sublines, E9 (androgen-low-sensitive), and AIDL (androgen-insensitive), were recombined with androgendependent embryonic rat urogenital sinus mesenchyme (UGM). Tumors of E9CUGM and AIDLCUGM were approximately three times as large as those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…AIDL cells were cultured in phenol red-free RPMI-1640 supplemented with 10% charcoal-stripped (CS) FBS and 1% antibiotic/antimycotic solution. The parental LNCaP, E9, and AIDL lines expressed similar levels of androgen receptor in culture, but prostate-specific antigen (PSA) protein was detected only in parental LNCaP cells (19). The androgen sensitivity of parental LNCaP, E9, and AIDL was confirmed by the change of PSA mRNA expression in cell culture with synthetic androgen R1881 (19).…”
Section: Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…AIDL cells were cultured in phenol red-free RPMI-1640 supplemented with 10% charcoal-stripped (CS) FBS and 1% antibiotic/antimycotic solution. The parental LNCaP, E9, and AIDL lines expressed similar levels of androgen receptor in culture, but prostate-specific antigen (PSA) protein was detected only in parental LNCaP cells (19). The androgen sensitivity of parental LNCaP, E9, and AIDL was confirmed by the change of PSA mRNA expression in cell culture with synthetic androgen R1881 (19).…”
Section: Cell Culturesmentioning
confidence: 99%
“…The parental LNCaP, E9, and AIDL lines expressed similar levels of androgen receptor in culture, but prostate-specific antigen (PSA) protein was detected only in parental LNCaP cells (19). The androgen sensitivity of parental LNCaP, E9, and AIDL was confirmed by the change of PSA mRNA expression in cell culture with synthetic androgen R1881 (19). Human prostate stromal cell PrSC was purchased from Lonza Group Ltd. PrSC was maintained using SCGM Bullet Kit (Lonza Group Ltd) as recommended.…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracted protein was separated by gel electrophoresis and transferred to Immobilon polyvinylidene difluoride membranes following our previously reported protocol. 17 Co-Culture of Prostate Epithelial Cell Lines (LNCaP, 22Rv1, and RWPE-1) with Fibroblasts LNCaP, 22Rv1, and RWPE-1 cells were co-cultured with each of the four fibroblast lines (PrSC, pcPrF-M5, pcPrF-M6, and pcPrF-M7) in six-well plates using cell culture inserts (BD Falcon, Franklin Lakes, NJ, USA). LNCaP, 22Rv1, and RWPE-1 cells (4 × 10 4 cells/well) were seeded into six-well plates in their respective recommended medium, while fibroblasts (PrSC, pcPrF-M5, pcPrF-M6, and pcPrF-M7; 2 × 10 4 cells/well) were seeded in SCBM media into cell culture inserts for 2 days.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…16 Several studies have reported that androgen-sensitive and -insensitive interactions between stromal and epithelial cells determine how prostate epithelial cells respond to androgen ablation. 17,18 In a low-androgen environment, stromal-epithelial interactions may be an important mechanism controlling AR activity and AR-regulated PSA expression.…”
mentioning
confidence: 99%